2019
DOI: 10.21608/assjm.2019.42147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing and Nitrogen Application Methods on Yield and Yield Components of Some Wheat Varieties

Abstract: Two field experiments were conducted at the Experiment and Research Center, Fac. Agric., Moshtohor, Benha Univ., during 2014/15 and 2015/16 seasons. The aim of this study was response to investigate the effect of three wheat varieties (Misr 2, Sakha 94 ,and Sids 12)to four planting methods (prodcasting, rows, hills on ridges and rows on beds ) and two application methods (prodcasting and drilling). The results indicated that:Misr 2 variety gave the highest values of plant height, spike length, No. tillers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…It can be concluded that the increasing amount of nitrogen fertilizer consequently results in higher grain yield. These results are in conformity with El-Gizawy (2005) [6] ; Mosaad et al, (2013) [21] and Gazia and Abd EL Aziz (2013) [7] . Data pertaining to fig.…”
Section: Grain Yield (Q/ha)supporting
confidence: 91%
“…It can be concluded that the increasing amount of nitrogen fertilizer consequently results in higher grain yield. These results are in conformity with El-Gizawy (2005) [6] ; Mosaad et al, (2013) [21] and Gazia and Abd EL Aziz (2013) [7] . Data pertaining to fig.…”
Section: Grain Yield (Q/ha)supporting
confidence: 91%
“…These results confirmed with those reported by Moussa and Abdel-Maksoud, (2004) where they found that, eight wheat cultivars differed significantly for number of spikes/m 2 , number of grains/spike, 1000grain weight, straw and grain yields. El-Gizawy, (2005) found that Gemmeiza 9 surpassed the other two cultivars in number of spikes/m 2 number of grains/spike, 1000-grain weight and grain yield. Gab Alla (2007) showed that, highly significant differences among 10 wheat genotypes in number of spikes/m 2 , number of grains/spike, 1000-grain weight, grain and straw yields and harvest index.…”
Section: Data Presented In Table (mentioning
confidence: 89%
“…The flower inducing domain of salicylic acid is important phytohormone that can enhance flowering in a variety of ornamental plants. Foliar application of brassinosteroid [4], salicylic acid [5] and cycocel [6] have been reported to be effective for enhancing mustard and other crops productivity by some worker under different environmental condition. It has been reported that these bio-regulators play vital role in greater participating of photosynthates toward reproductive sink thereby improving harvest index.…”
Section: Introductionmentioning
confidence: 99%